Contribution of actin filaments and microtubules to cell elongation and alignment depends on the grating depth of microgratings. Issue 1 (December 2016) - Lee, Kyunghee; Kim, Ee; Oh, Naeun; Tuan, Nguyen; Bae, Nam; Lee, Seok; Lee, Kyoung; Eom, Chi-Yong; Yim, Evelyn; Park, Sungsu
Abstract Background It has been reported that both chemical and physical surface patterns influence cellular behaviors, such as cell alignment and elongation. However, it still remains unclear how actin filament and microtubules (MTs) differentially respond to these patterns. Results We examined the effects of chemical and physical patterns on cell elongation and alignment by observing actin filament and MTs of retinal pigment epithelium- 1(RPE-1) cells, which were cultured on either fibronectin (FN)-line pattern (line width and spacing: 1 μm) or FN-coated 1 μm gratings with two different depths (0.35 or 1 μm). On the surface with either FN-line pattern or micrograting structure, the cell aspect ratios were at least two times higher than those on the surface with no pattern. Cell elongation on the gratings depended on the depth of the gratings. Cell elongation and alignment on both FN-line pattern and 1 μm gratings with 0.35 μm depth were perturbed either by inhibition of actin polymerization or MT depletion, while cell elongation and alignment on 1 μm gratings with 1 μm depth were perturbed only by MT depletion. Conclusions Our results suggest that the contribution of actin filaments and MTs to the elongation and alignment of epithelial cells on microgratings depends on the groove depth of these gratings.